Policy advice: markets and policies - Renzo Orsi; Katarzyna Zukrowska (Free University Berlin, Jean Monnet Centre of Excellence, 2004)
This paper aims at the provision of applicable recommendations for institutions and actors involved regarding the EMU accession process both in CEE and in the euro-zone. In order to provide topical advice, the first part, on markets, will concentrate on theory and empirics of labour markets, financial markets and foreign direct investment, whereas the second part, dealing with policies, will put emphasis on exchange rates, FDI, labour markets, and the social dimension. It turns out that benefits and losses of EMU accession may differ with regard to the different issue areas. To get to clear-cut recommendations, diverging impacts and their balance have been taken into consideration. Special regard has been given to divergent groups of winners and losers during accession, its impact on the political decision -making process, and ways to compensate for them.
Keywords: E0; E5; E6; D6; F0; F1; F2; F4; H5; G1; J2; J3; J6; 330; Eu enlargement; monetary integration; economic integration; EMU; ERM 2; trade and FDI; financial markets; fiscal and monetary policy; labour markets; social policies; exchange rate regimes for CEE